PERFORMANCE ANALYSIS OF REALIZATION OF REGIONAL INCOME AND EXPENDITURE BUDGET (APBD) REVIEWED FROM FINANCIAL RATIO - Suandi, Suandi; Pahmi, Saepul (Universitas Gajah Putih, 2020)
This study aims to determine the financial performance of the NTB provincial government by using financial statement analysis of the NTB provincial revenue and expenditure budget for the 2010-2017 fiscal year. The type of research used in this research is comparative descriptive. The processed money data is a summary of the regional income and expenditure budget for the 2010-2017 fiscal year obtained from the regional financial and asset management agency. The results of the study show that: 1) regional growth and spending are good; 2) the level of independence of the NTB province is classified as participatory; 3) the level of effectiveness of the province of NTB is quite effective; 4) the efficiency level of the province of NTB is classified as very efficient; 5) the degree of fiscal decentralization is quite sufficient; 6) the allocation of funds for operating expenditures is prioritized over capital expenditures. Based on the calculation results, it can be concluded that the financial performance of the province of NTB is quite effective and very efficient. Thus, government management must be willing to increase and maximize PAD for the following years.